Wise Leader Strategies: Building Trust and Long-Term Success - Jumadi, Jumadi; Yasa, I Made Ardika; Yudana , I Made (Journal of Management Economic and Financial, 2023)
This article is structured with descriptive qualitative research methods, discussing wise leaders' strategies in building trust and achieving long-term success. Wise leaders are those who are able to integrate knowledge, experience, and intuition to make informed decisions in the face of complex and dynamic challenges who are able to steer their teams through the changes necessary to achieve organizational goals. One important aspect of a wise leader's strategy is the ability to listen and understand the perspectives of others so as to create an inclusive work climate, where all team members feel heard, valued, and motivated to make their best contribution. In making decisions, wise leaders also consider various points of view and gather input from team members before making a final decision. In addition, wise leaders have the ability to manage conflict wisely and are able to recognize and resolve conflicts in constructive ways, promote open communication, and seek the best solutions to resolve problems. Wise leaders also encourage effective collaboration and teamwork, building strong and mutually beneficial relationships between team members. Furthermore, wise leaders also have a long-term vision and ability to anticipate upcoming changes through careful strategic planning, evaluating market trends, and predicting their impact on the organization and being open to innovation and change so as to inspire teams to adapt and grow together. In this article, we will also discuss the implementation of wise leader strategies. By practicing wise leader strategies, leaders can build trust, manage change, and achieve long-term success for the organization.